THE HYDROGEOCHEMISTRY OF A HEAVILY USED AQUIFER IN THE MEXICAN WINE-PRODUCING GUADALUPE VALLEY, BAJA CALIFORNIA - Daesslé L.W.; Mendoza-espinosa L.G.; Camacho-ibar V.F.; Rozier W.; Morton O.; Van dorst L.; Lugo-ibarra K.C.; Quintanilla-montoya A.L.; Rodríguez-pinal A. (My University, 2006)
The Guadalupe Valley aquifer is the only water source for one of the most important wine industries in Mexico, and also the main public water supply for the nearby city of Ensenada. This groundwater is monitored for major ion, N-NO3, P-PO4, Fe, As, Se, Mo, Cd, Cu, Pb, Zn and Sb concentrations, as well as TDS, pH, dissolved oxygen and temperature. High concentrations of N-NO3 (26 mg l−1), Se (70 μg l−1), Mo (18 μg l−1) and Cu (4.3 μg l−1) suggest that groundwater is being polluted by the use of fertilizers only in the western section of the aquifer, known as El Porvenir graben. Unlike the sites located near the main recharge area to the East of the aquifer, the water in El Porvenir graben has low tritium concentrations (<1.9 TU), indicating a pre-modern age, and thus longer water residence time. No significant variations in water quality (generally <10%) were detected throughout 2001–2002 in the aquifer, suggesting that reduced rainfall and recharge during this dry period did not significantly affect water quality. However, the wells nearest to the main recharge area in the Eastern aquifer show a slight but constant increase in TDS with time, probably as a result of the high (~200 L S−1) uninterrupted extraction of water at this specific recharge site. Relatively high As concentrations for the aquifer (10.5 μg l−1) are only found near the northern limit of the basin associated with a geological fault.
Keywords: MEXICO; BAJA CALIFORNIA; GUADALUPE VALLEY; GROUNDWATER; PHOSPHATE; NITRATE; FERTILIZERS